Reconstruction of mandibular defects using synthetic octacalcium phosphate combined with bone matrix gelatin in rat model - Fereydoon Sargolzaei-Aval; Eshagh Ali Saberi; Mohammad Reza Arab; Narjes Sargolzaei; Esmaeel Zare; Heshmatollah Shahraki; Tayebeh Sanchooli; Forough Sargolzaeiaval; Maryam Arab (Wolters Kluwer Medknow Publications, 2020)
Background: Regeneration of bone defects remains a challenge for maxillofacial surgeons. The objective of this study was to assess the osteogenic potential of octacalcium phosphate (OCP) and bone matrix gelatin (BMG) alone and in combination with together in artificially created mandibular bone defects. Materials and Methods: In this experimental study Forty-eight male Sprague-Dawley rats (6-8 weeks old) were randomly divided into four groups. Defects were created in the mandible of rats and filled with 10 mg of OCP, BMG, or a combination of both (1/4 ratio). Defects were left unfilled in the control group. To assess bone regeneration and determine the amount of the newly formed bone, specimens were harvested at 7, 14, 21, and 56 days postimplantation. The specimens were processed routinely and studied histologically and histomorphometrically using the light microscope and eyepiece graticule. The amount of newly formed bone was quantitatively measured using histomorphometric methods. Histomorphometric data were analyzed using SPSS software. Mean, standard deviation, mode, and medians were calculated. Tukey HSD test was used to compare the means in all groups. P < 0.05 was considered as statistically significant (i.e., 5% significant level). Results: In the experimental groups, the new bone formation was initiated from the margin of defects during the 7-14 days after implantation. By the end of study, the amount of newly formed bone increased and relatively matured, and almost all of the implanted materials were absorbed. In the control group, slight amount of new bone had been formed at the defect margins (next to the host bone) on day 56. The histomorphometric analysis revealed statistically significant differences in the amount of newly formed bone between the experimental and the control groups (P < 0.001). Conclusion: Combination of OCP/BMG may serve as an optimal biomaterial for the treatment of mandibular bone defects.